Comparative Information Technology
200 p.
Keywords: This volume offers a critique of the nexus between ICT and its impact on society, individuals and educational institutions. One of the most significant dimensions of globalisation has been the rapid development of information and communications technologies (ICTs). Our lives have been changed by ICTs in numerous ways and the implications for education are enormous. The ICTs have transformed the linguistic, cognitive and visual dimensions of human communication, as well as our perceptions of the self, and social identity in the global culture. They have facilitated the development of new dimensions of digital literacy, such as blogging and sms messaging. In this sense, cyberlanguage continues to evolve by borrowing and adapting familiar words, coining new expressions, and embracing particular styles. The book provides directions in education and policy research, relevant to transformational educational reforms in the 21st century.